The contrast between rural and urban life in 19th century French literature - Editor, Hayitgul (The Lingua Spectrum, 2025)
This article analyzes the contrast between rural and urban life in 19th century French literature. It examines how the social changes resulting from widespread industrialization and urban growth were reflected in the works of prominent writers of the period. The study analyzes the works of Honoré de Balzac, Guy de Maupassant, Émile Zola, Gustave Flaubert, and other writers, revealing literary portrayals of rural and urban life and the literary and socio-historical context of the contrast between them. The article explores how French literature reflected the complex consequences of urbanization and industrialization processes, their impact on society, people, and values, showing the fundamental contradictions: naturalness and artificiality, tradition and modernism, community and individual, progress and decline.